2015
DOI: 10.1212/wnl.0000000000001238
|View full text |Cite
|
Sign up to set email alerts
|

“Noncognitive” symptoms of early Alzheimer disease

Abstract: Objectives: To observe the natural time course of noncognitive symptoms before the onset of symptomatic Alzheimer disease dementia.Methods: Using the National Alzheimer's Coordinating Center Uniform Data Set from September 2005 to March 2013, data from cognitively normal individuals who were aged 50 years or older at first visit and had subsequent follow-up were analyzed. Survival analyses were used to examine the development of particular symptoms relative to each other on the Neuropsychiatric Inventory Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
117
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 22 publications
13
117
1
2
Order By: Relevance
“…The lack of a relationship between measures of mood and the biomarkers at baseline together with the finding that participants with more abnormal biomarker values at baseline had higher change scores on mood measures (i.e., increasing mood disturbance) across a short follow-up period (one-year) suggests that the presence of abnormal AD biomarker levels are associated with a measurable impact on mood as the disease processes, although these changes are subtle and may not be recognized without formal testing. These findings extend our previous work 26 on the development of depressive and neuropsychiatric symptoms in participants with CDR > 0.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of a relationship between measures of mood and the biomarkers at baseline together with the finding that participants with more abnormal biomarker values at baseline had higher change scores on mood measures (i.e., increasing mood disturbance) across a short follow-up period (one-year) suggests that the presence of abnormal AD biomarker levels are associated with a measurable impact on mood as the disease processes, although these changes are subtle and may not be recognized without formal testing. These findings extend our previous work 26 on the development of depressive and neuropsychiatric symptoms in participants with CDR > 0.…”
Section: Discussionsupporting
confidence: 90%
“…These declines, however, were somewhat lower than would be expected by the average progression of treated AD. Our patients had a stability of psychiatric symptoms assessed by the NPI-Q, while other studies observed a worsening of depressive symptoms in this kind of patients [43]. …”
Section: Discussionsupporting
confidence: 49%
“…These changes may be related to preexisting deficits in the integrity of the frontal tracts that have been observed in individuals with DS 44 and that may be worsened by Aβ deposition in the frontal lobes 45 . Although BPSDs are very prominent in early AD-DS, this presentation is not unique to these individuals -it also occurs, albeit at lower rates, during the early stages of LOAD 46 and EOAD 47 , particularly in cases arising from mutations in the AD risk gene presenilin 1 (PSEN1; which maps to chromosome 14). Further studies are required to determine the earliest changes associated with the development of dementia in people who have DS, and to delineate other clinical differences between AD-DS, LOAD and familial forms of EOAD, such as the frequencies of co-morbidities that may affect the onset and progression of dementia (for example, cardiovascular disease and systemic infections).…”
Section: Clinical Features Of Ad-dsmentioning
confidence: 99%